Influence of contact network parameters on value of current rise speed during short circuit in power circuits of electric rolling stock - Karzova, O. A. (Science and Transport Progress, 2014)
Purpose. Influence investigation of contact system parameters on current rate of rise during short circuit, and the difference of these parameter values under different connection diagrams of traction motors in the power circuit. Methodology. The mathematical model and method for determining the effect of the contact system parameters, such as inductance and active resistance of the contact wire, on rise speed during the short circuit current were offered. Besides that, it is determined the influence of current speeds on their difference in power circuits of DC electric locomotive in different points of short circuit, different variants of traction electric engines connection and different distances of electric locomotives from the traction substation. The proposed model and method can be used for any type of electric DC locomotive at any point of a short circuit in traction engine circuit. Findings. Qualitative and quantitative influence of contact system parameters on values of current rise speed during short circuit and on the differences value of these parameters with different connection diagram of traction electric engines was established. Originality. The investigation method concerning determination of the influence of contact system parameters on current rise speed in short circuit and on the difference of these parameters on different distances of electric locomotives from traction substation was proposed. Practical value. The results can be used in selection of protective devices of rolling stock power circuits, where the main parameter is the current rise speed during the short circuit.